The effect of intrarectal paclitaxel lavage on the healing of rectal anastomosis: A comparison with povidone iodine - (:unkn) unknown (Turkiye Klinikleri, 2005)
Objective: Intraluminal colonic washout with anticancer agents is an alternative option to prevent local recurrences after colorectal cancer resection. However, intracolonic washout with any agent can interfere with anastomotic wound healing. The current study aimed to investigate the effects of intracolonic paclitaxel and povidone-iodine administration on intestinal anastomotic healing. Material and Methods: Localized intracolonic washout with paclitaxel (3 mg/kg) and povidone-iodine (5%) was achieved before and after colorectal anastomosis in two (each consisting of 10) groups of rats. The control group (n= 10) received no medical therapy. Anastomotic bursting pressures, anastomotic hydroxyproline content, and peri-anastomotic myeloperoxidase activity were determined. Results: Bursting pressure was significantly less in the povidone group, while it was slightly elevated in the paclitaxel group when compared to the control group. The hydroxyproline level was significantly increased in the povidone group, while it was found to be decreased in the paclitaxel group. Myeloperoxidase levels were also significantly decreased in both groups when compared to the control group. Conclusion: Although paclitaxel decreases hydroxyproline production, it does not appear to affect anastomotic bursting pressure. Conversely, povidone-iodine decreases anastomotic bursting pressure despite increased hydroxproline synthesis. These data imply that paclitaxel and povidone-iodine carry out their effects on anastomotic healing either by altering the quality or quantity of collagen synthesis. Copyright © 2005 by Türkiye Klinikleri.
Keywords: Colon; Paclitaxel; Povidone-iodine